Biologia das interações entre os visitantes florais (Hymenoptera, Apidae) e Tibouchina pulchra Cogn. (Melastomataceae) - Silva, Juliana Bertolino da (2006)
Orientador: Gabriel Augusto Rodrigues de Melo